Impaired muscle morphology in a Drosophila model of myosin storage myopathy was suppressed by overexpression of an E3 ubiquitin ligase - Martin Dahl-Halvarsson; Montse Olive; Malgorzata Pokrzywa; Michaela Norum; Katarina Ejeskär; Homa Tajsharghi (The Company of Biologists, 2020)
Myosin is vital for body movement and heart contractility. Mutations in MYH7, encoding slow/β-cardiac myosin heavy chain, are an important cause of hypertrophic and dilated cardiomyopathy, as well as skeletal muscle disease. A dominant missense mutation (R1845W) in MYH7 has been reported in several unrelated cases of myosin storage myopathy. We have developed a Drosophila model for a myosin storage myopathy in order to investigate the dose-dependent mechanisms underlying the pathological roles of the R1845W mutation. This study shows that a higher expression level of the mutated allele is concomitant with severe impairment of muscle function and progressively disrupted muscle morphology. The impaired muscle morphology associated with the mutant allele was suppressed by expression of Thin (herein referred to as Abba), an E3 ubiquitin ligase. This Drosophila model recapitulates pathological features seen in myopathy patients with the R1845W mutation and severe ultrastructural abnormalities, including extensive loss of thick filaments with selective A-band loss, and preservation of I-band and Z-disks were observed in indirect flight muscles of flies with exclusive expression of mutant myosin. Furthermore, the impaired muscle morphology associated with the mutant allele was suppressed by expression of Abba. These findings suggest that modification of the ubiquitin proteasome system may be beneficial in myosin storage myopathy by reducing the impact of MYH7 mutation in patients.